Effect of VAM on Growth and Development of Bamboos Planted under Agroforestry System - Nema, Sharad; Behari, Bipin; , Jamaluddin (Indian Forester, 1998)
The growth performance of three bamboo species namely Bambusa bambos, Dendrocalamus strictus and Bambusa nutans was studied in four sites of agricultural fields. The sites II and III were more or less same in soil texture and nutrient status. The species of bamboo were inoculated with VAM fungi including Glomus mosseae, G. intraratices, Gigaspora species and Acaulospora species. The suitable control was maintained without VAM inoculation. Comparatively the response of VAM inoculation was better in site I. Bambusa bambos showed significant difference in the length of leading shoots compared with other two species of bamboo. Similarly the per cent infection was more in bamboo species planted in sites I, II and III. The spore population did not exhibit any significant variation in bamboo species inoculated and uninoculated (control) with VAM fungi.